Ectoparasites of Sheep, Their Treatment and Prevention Measures - Jabborov, G. G. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information based on the analysis of the literature on ectoparasites, which partially hinders the development of sheep breeding, one of the leading sectors of animal husbandry in the country.